Preparation of graphene-based aerogels by Pickering emulsion method and their performance. Issue 6 (3rd June 2021) - Liu, Huie; Xiang, Xiaoxiao; Liu, Zexin; Yang, Fan; Lin, Zimei; Chen, Shuang; Xu, Guoqiang
Abstract: Pickering emulsion were used as soft template for the preparation of two different kinds of graphene-based aerogels (graphene aerogels, named AGAs and graphene/polyvinyl alcohol (PVA) aerogels, named BGAs) in this work. The Pickering emulsions show good control effect on the pore sizes, density and porosity of the two kinds of graphene-based aerogels. The increase of the oil/water ratio in the emulsion can leads to increase of pore size and porosity and decrease of density of AGAs and BGAs. And the increase of agitation speed during the emulsion preparation leads to the decrease of the pore sizes of AGAs and BGAs, while shows slight influence on the porosity and density of the materials. Volume filling behavior was found when AGAs and BGAs adsorbing organics, so it is considered that high porosity and high open pore fraction in the aerogels will favor the adsorption capacity on organics.